2011
DOI: 10.1161/circulationaha.110.013466
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After In-Hospital Cardiac Arrest in Children With Cardiac Disease

Abstract: Background— Small studies suggest that children experiencing a cardiac arrest after undergoing cardiac surgery have better outcomes than other groups of patients, but the survival outcomes and periarrest variables of cardiac and noncardiac pediatric patients have not been compared. Methods and Results— All cardiac arrests in patients <18 years of age were identified from Get With the Guidelines–Resuscitation from 2000 to 2008. Cardiac arrests occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 27 publications
6
97
1
4
Order By: Relevance
“…16 Review of cardiac surgical data at our institution demonstrates that our overall incidence of cardiopulmonary arrests is similar to the incidences reported in other published data series 3,4,17 at 3% to 6% per year. The Get With The Guidelines-Resuscitation database www.ajcconline.org report 13 from 2011 reported a subgroup of cardiac surgical patients with a survival to discharge of 37%, which was similar to our experience in 2010 and 2011. Over time, our survival rate after cardiopulmonary arrest has improved each year with survival to discharge reaching 55% in 2012 and 81% in 2013, exceeding reported survival rates of 37% to 48% in this specific population.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…16 Review of cardiac surgical data at our institution demonstrates that our overall incidence of cardiopulmonary arrests is similar to the incidences reported in other published data series 3,4,17 at 3% to 6% per year. The Get With The Guidelines-Resuscitation database www.ajcconline.org report 13 from 2011 reported a subgroup of cardiac surgical patients with a survival to discharge of 37%, which was similar to our experience in 2010 and 2011. Over time, our survival rate after cardiopulmonary arrest has improved each year with survival to discharge reaching 55% in 2012 and 81% in 2013, exceeding reported survival rates of 37% to 48% in this specific population.…”
Section: Discussionsupporting
confidence: 85%
“…Over time, our survival rate after cardiopulmonary arrest has improved each year with survival to discharge reaching 55% in 2012 and 81% in 2013, exceeding reported survival rates of 37% to 48% in this specific population. 13,17 This survival rate would suggest that our heart center has lowered our failure-to-rescue rate specifically related to cardiopulmonary arrests in the cardiac surgical patients. Additionally, we have noticed a downward trend, which is not yet significant, in the percentage of cardiopulmonary arrests deemed "potentially preventable."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified low-quality evidence (downgraded for indirectness, inconsistency, and residual confounding) from a single pediatric study of IHCA 76 that showed benefit to ECPR when compared with CPR without the use of ECMO (OR, 2.5; 95% CI, 1.3-4.5; P50.007 in surgical cardiac diagnoses; OR, 3.8; 95% CI, 1.4-5.8; P50.011 in medical cardiac diagnoses).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…25 Observational data support the use of ECPR for infants and children in cardiac arrest (especially those with underlying cardiac disease) in the in-hospital critical care setting, when patients are refractory to conventional resuscitation, and when the necessary ECPR protocols, expertise, and equipment exist. 26,27 No evidence exists to support its routine use for cardiac arrest in the out-of-hospital setting.…”
Section: Intra-arrestmentioning
confidence: 99%